Analysis of the Influence Islamic Branding on the Intention of the Community in Gowa District to Become Customers of Bank Syariah Indonesia (BSI) - Akib, Baso; Nur, Apriyansyah; Handayani, Lilies (Indonesian Journal Publisher, 2023)
The research is aimed at: (1) knowing the influence of Islamic branding on public interest in becoming a customer at BSI Branch Gowa; (2) finding out the impact of Shariah financial literature on the interest of the public being a customer at BSI Gowa Branch; (3) knowing about the effect of service quality on the public's interest in becoming a customer; and (4) learning about the influences of Muslim branding, shariah finance literature, and service quality on public interest in becoming a client at BSI Branch Gowa. This type of research is quantitative and descriptive. The data used is primary data. Primary data is collected using questionnaires, observations, and documentation. double-linear regression test analysis method. Sampling is a simple, random sampling technique. The sample used as many as 80 respondents, and data analysis was done using IBM SPSS 28. The results of this study show that: (1) Islamic branding has no positive and non-significant influence on public interest in BSI Gowa Branch; (2) Shariah financial literacy has a positive and significant influence upon public interest to become a customer of BSI Gowa Branch; (3) Service quality has a negative and significant impact on the interest of the public in becoming a customer; and (4) Islamic branding, Sharial literature, and Service quality have a positive and significant effect on the public's interest in being a customer at BSI Gowa Branch. Implications in this study are that Islamic branding has become an early reflection of BSI Gowa branch operating in accordance with the principle of shariah, even though the public is not fully aware of this. A high level of understanding of the sharial financial literature can give a boost to the public, especially about BSI Gwang Gowa branch, and good service quality is able to have a positive impact on the development of BSI Gowa branches.